Perception on environmental conservation in Similajau National Park Sarawak, Malaysia - Hassan, Suziana; Sim, Kah Ching; Ismail, Zahora; Md Allwi, Norul Izani; Rosli, Zamri (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
This study interprets the findings for the development of key factors that determine the customers’ perception for on conserving the Similajau National Park (SNP) using Likert scale. Information from previous studies related to perception on ecotourism are combined with newly found variables obtained through initial visits to the study site have produced a new set of measurement scale. Factor analysis is used as a data reduction method. The significant variables are extracted and regrouped accordingly into several factors that generate a new set of scales. As a result, 25 perceptions are derived that significantly contribute in determining the customers’ perception on SNP for conservation purposes; the variables are regrouped into 2 thematic indicators. The indicators as perceived by the visitors could be useful for the management in future conservation of the National Park and in the provision of essential services and facilities.